Ring, ring, ring… are you dreaming?: combining acoustic stimulation and reality testing for lucid dream induction: a sleep laboratory study - Erlacher, Daniel; Schmid, Daniel; Bischof, Florian; Hammer, Jennifer; Stumbrys, Tadas (International journal of dream research, 2020)
Lucid dreaming, the fact that one knows that they are dreaming while dreaming, provides a unique paradigm for the study of the distinctive psychophysiological state of dreaming and consciousness. Unfortunately, frequent lucid dreamers are rare and techniques should be established to reliably induce lucid dreams. Here the induction of lucid dreams with a combination of reality testing and the external auditory stimulation with ring tones was applied. The procedure induced a self-rated lucid dream in five participants compared to one lucid dream in a sham condition. In two cases (16.7%) a signal-verified lucid dream was found. The induction rate of the present study procedure will be discussed in the context of previous studies and success rates of combining reality checking with external stimulation.
Gesehen am 21.10.2020